HUBUNGAN TINGKAT SUKU BUNGA SERTIFIKAT BANK INDONESIA (SBI), INFLASI, DAN INDEKS HARGA SAHAM GABUNGAN (IHSG) - setiawan, Adi (Benefit: Jurnal Manajemen dan Bisnis, 2009)
This study aims to determine whether there is a significant reciprocal relationship between inflation with interest rate of Bank Indonesia Certificates (SBI), the interest rate of Bank Indonesia Certificates (SBI) with the Composite Index (JCI), and between inflation with Stock Price Index (JCI) using Stasionairity test data, test of Granger Causality, and test VectorAuto Regression (VAR) for the period January 2006 - December 2010. Results of analysis of this study indicate there is a significant reciprocal relationship between inflation with interest rate of Bank Indonesia Certificates (SBIs), but there is no significant reciprocal relationship between the interest rate of Bank Indonesia Certificates (SBI) with the Composite Index (JCI) ; and also there is no significant reciprocal relationship between the inflation with Composite Stock Price Index (CSPI).